A nonlinear multi-period hydrothermal optimal power flow model for hydropower systems - Nerger, Amanda [UNESP]; Martins, André Christóvão Pio [UNESP]; Soler, Edilaine Martins [UNESP]; Balbo, Antonio Roberto [UNESP]; Nepomuceno, Leonardo [UNESP] (Elsevier, 2024)
Despite their social and climate benefits, renewable energy sources also present challenges such as intermittency, volatility and randomness, which may considerably reduce security and reliability of the system. Hydro units have the ability to provide flexible and rapid energy reserves, serving as an effective way of handling these challenges. Yet, many Hydrothermal Optimal Power Flow (HOPF) models in the literature often provide a simplified and sometimes inaccurate representation of the hydraulic aspects. In most HPOF models proposed in the literature, the representation of hydraulic aspects disregards important physical and operational hydro constraints. Such simplifications can curtail the potential benefits of hydro generation, especially concerning system security and reliability. In this paper, we investigate the impact of hydro constraints in the operation of hydrothermal systems by means of HOPF models. For such a purpose, we propose a nonlinear multi-period active–reactive HOPF model where hydro constraints are represented in detail, by means of a nonlinear framework. This model presents innovative formulations for hydro units, specifically designed to address pivotal non-differentiable constraints. The proposed multi-period HOPF model is used as a benchmark to assess inaccuracies present in linear or linearized HOPF model variants. The results using the IEEE 24-bus and 300-bus systems, adapted so they become hydropower systems, clearly identify significant impact of some hydro constraints which have been neglected in most models described in the literature, in the hydrothermal operational policy and scheduling.
Keywords: Hydrothermal optimal power flow; Optimal power flow; Short-term hydrothermal scheduling